2015
DOI: 10.1186/s12943-015-0397-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis and selective small molecule inhibition identifies BCL-XL as a critical survival factor in a subset of colorectal cancer

Abstract: BackgroundDefects in programmed cell death, or apoptosis, are a hallmark of cancer. The anti-apoptotic B-cell lymphoma 2 (BCL-2) family proteins, including BCL-2, BCL-XL, and MCL-1 have been characterized as key survival factors in multiple cancer types. Because cancer types with BCL2 and MCL1 amplification are more prone to inhibition of their respectively encoded proteins, we hypothesized that cancers with a significant frequency of BCL2L1 amplification would have greater dependency on BCL-XL for survival.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 31 publications
4
38
2
Order By: Relevance
“…Inhibiting a single pro-survival homolog had little effect on short-term survival; only SW48 cells showed greater than a 50% decrease in viability after treatment with A-1331852, consistent with a previous study showing SW48 is sensitive to Bcl-xL inhibition (Zhang et al, 2015; Figure 9A). Combined inhibition of both Mcl-1 and Bcl-xL caused nearly complete cell death after 24 hr in all colon cancers except HCT-116; further analyses showed that αMCL1-mediated Mcl-1 inhibition strongly sensitizes most colon cancers to A-1331852 (and to a lesser extent ABT-263), with a 4.6-fold or greater decrease in EC 50 values observed in all cell lines except HCT-116 (Figure 9—figure supplement 1A–B).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Inhibiting a single pro-survival homolog had little effect on short-term survival; only SW48 cells showed greater than a 50% decrease in viability after treatment with A-1331852, consistent with a previous study showing SW48 is sensitive to Bcl-xL inhibition (Zhang et al, 2015; Figure 9A). Combined inhibition of both Mcl-1 and Bcl-xL caused nearly complete cell death after 24 hr in all colon cancers except HCT-116; further analyses showed that αMCL1-mediated Mcl-1 inhibition strongly sensitizes most colon cancers to A-1331852 (and to a lesser extent ABT-263), with a 4.6-fold or greater decrease in EC 50 values observed in all cell lines except HCT-116 (Figure 9—figure supplement 1A–B).…”
Section: Resultssupporting
confidence: 91%
“…In previous studies, colon cancers showed a variable response to small-molecule-mediated Bcl-xL inhibition, and RNAi experiments identified Mcl-1 as a resistance factor (Zhang et al, 2015). To determine whether the Mcl-1 antagonism could render colon cancers sensitive to Bcl-xL neutralization and assess the influence of other pro-survival homologs on survival, we modified a panel of seven colon cancer lines to inducibly express either αMCL1 or αBFL1, and treated them with small molecules to selectively inhibit Bcl-2 (ABT-199), Bcl-xL (A-1331852), or Bcl-2 and Bcl-xL simultaneously (ABT-263).…”
Section: Resultsmentioning
confidence: 99%
“…24, 25 Furthermore, Bcl-x L has been identified as a critical survival factor utilizing frequent genomic alterations in a subset of CRCs. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Anti-apoptotic proteins include at least BCL-2, BCL-xL, MCL-1, BCL-w and BFL-1. High expression of anti-apoptotic proteins, especially BCL-211, 12, 13, 14, BCL-xL 15 and MCL-116, 17, 18, 19, 20, has been shown in various types of cancers, and they play important roles in tumorigenesis in different tumor models 9, 21, 22, 23, 24, 25. Pro-apoptotic proteins can be further divided into two subgroups, including multi-domain proteins, like the death effectors/executioners BAX and BAK; and BH3-only proteins, like activators BIM, BID and PUMA, or sensitizers including BAD, NOXA, HRK and BMF.…”
Section: Apoptosis Is Regulated By Bcl-2 Family Proteinsmentioning
confidence: 99%